A Simple Approach for Pilot Analysis of Time-Dependent Enzyme Inhibition: Discrimination Between Mechanism-Based Inactivation and Tight Binding Inhibitor Behavior - Buneeva, O.A.; Aksenova, L.N.; Medvedev, A.E. (Biomedical Chemistry: Research and Methods, 2020)
The increase in enzyme inhibition developed during prolonged incubation of an enzyme preparation with a chemical substance may be associated with both the non-covalent and also with covalent enzyme-inhibitor complex formation. The latter case involves catalytic conversion of a mechanism-based irreversible inhibitor (a poor substrate) into a reactive species forming covalent adduct(s) with the enzyme and thus irreversibly inactivating the enzyme molecule. Using a simple approach, based on comparison of enzyme inhibition after preincubation with a potential inhibitor at 4ºC or 37ºC we have analyzed inhibition of monoamine oxidase A (MAO A) by known MAO inhibitors pargyline and pirlindole (pyrazidol). MAO A inhibitory activity of pirlindole (reversible tight binding inhibitor of MAO A) assayed after mitochondrial wash was basically the same for the incubation at both 4ºC and 37ºC. In contrast to pirlindole, the effect of pargyline (mechanism based irreversible MAO inhibitor) strongly depended on the temperature of the incubation medium. At 37ºC the residual activity MAO A in the mitochondrial fraction after washing was significantly lower than in the mitochondrial samples incubated with pargyline at 4ºC. Results of this study suggest that using analysis of both time- and temperature-dependence of inhibition it is possible to discriminate mechanism-based irreversible inhibition and reversible tight binding inhibition of target enzym